Is it or is it not she: Germaine de Staёl and the portrait painted by Borovikovsky - V. A. Milchina (Шаги)
In Tretyakov Gallery there is a portrait of a lady in a light green dress and turban, painted by Vladimir Lukich Borovikovsky. In the most recent catalogue, it is labelled as the portrait of Mme de Staёl, but this attribution is accompanied by a question mark in parentheses. The identification of Borovikovsky’s model as the famous French writer Germaine de Staёl (1766–1817) arose a century ago. Most likely, it was prompted by the unquestionable fact that in 1812 de Staёl spent three weeks in Petersburg, where Borovikovsky was living, as well as by similarities between the face of the woman depicted on the portrait with what is known about the appearance of the authoress. Until now no other proofs have been offered. The article discusses a number of Mme de Staёl’s “distinguishing features” which make quite clear her difference from the lady in the portrait. The latter wears a turban and Mme de Staёl did in fact like turbans; however, the turban in the portrait is pale green, while memoirists were unanimous in affirming, even many years later, that de Staёl’s turban was always red or crimson. The woman in the portrait is covered in jewels: a pearl bandeau, a bracelet, earrings, a necklace. No jewels are to be found on any of de Staёl’s known portraits. Finally, perhaps the main “clue”, or, more precisely, its absence. Everyone who wrote about de Staёl described a gesture which practically became her emblem: she always held in her hand a small green twig or a sheet of paper — this is how she is depicted on many French portraits. By contrast, Borovikovsky’s lady holds nothing in her hands. It is also significant that neither in her memoir, Ten Years of Exile, nor in her diary from 1812 does de Staёl mention sitting for a portrait. All this leads to the conclusion that someone else is depicted in Borovikovsky’s painting.